High-entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics as well as preparation method and application of high-entropy spinel ferrite catalyst

Through the photocatalytic technology of high-entropy spinel ferrite catalyst, the problem of difficult removal of dyes and antibiotics in industrial wastewater is solved, and efficient and environmentally friendly degradation effect is achieved, and the catalyst has good cycling performance.

CN119897115AActive Publication Date: 2025-04-29WUHAN INST OF TECH

Patent Information

Application Number
CN202510009906.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-29
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

It is difficult for the prior art to efficiently remove dyes and antibiotics from industrial wastewater, especially low concentrations of antibiotics. Traditional methods have problems with secondary pollution and low removal efficiency.

Method used

The Cu1/2Zn1/2Fe2/3Co2/3Ni2/3O4 catalyst was prepared by sol combustion method using high entropy spinel ferrite catalyst, and photocatalytic degradation was used to avoid the use of oxidants.

Benefits of technology

The photocatalytic degradation efficiency of dyes and antibiotics is significantly improved. The catalyst still maintains good activity after multiple cycles, and the degradation efficiency is higher than that of a single component oxide, and it conforms to the concept of green environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897115A_ABST
    Figure CN119897115A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics as well as a preparation method and application of the high-entropy spinel ferrite catalyst. The Cu1 / 2Zn1 / 2Fe2 / 3Co2 / 3Ni2 / 3O4 (HEO-FNCCZ) high-entropy spinel ferrite catalyst is prepared by adopting a sol combustion method, the photocatalytic degradation performance of common dyes and antibiotics is evaluated by simulating visible light photocatalysis, and the reaction mechanism of photocatalytic degradation of methylene blue with the best effect is researched. The photocatalytic reaction is effectively promoted by utilizing the catalytic effect of the spinel ferrite, so that environment-friendly pollutant degradation is realized. According to the method, the production process is simple, various organic toxic and harmful substances are not introduced, the method is nontoxic and harmless in the use process, the recovery efficiency of the catalyst exceeds 95%, and the method has the characteristics of remarkable degradation effect and no secondary pollution; the preparation method only relates to the processes of dissolving, calcining, crushing and the like, and is extremely suitable for industrial batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysis, spinel ferrite and pollutant degradation, and in particular to a high-entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics, and a preparation method and application thereof. Background Art

[0002] Industrial wastewater contains a large amount of dyes and antibiotics, which will cause serious pollution when discharged into the environment, and even threaten human survival and health. Methylene blue (MB) is a chemical dye commonly used in textile industrial wastewater. It has difficult-to-decompose chemical structures such as azo and nitro groups, is carcinogenic and toxic, and the inhibitory effect of antibiotics on microorganisms makes it difficult to effectively remove it by traditional processes. Advanced oxidation technology is usually required to degrade methylene blue into harmless products. Cefixime and tetracycline are commonly used drugs for bacterial infections in humans and animals. Their associated specific environmental risks have threatened human health. Effective removal of antibiotics from aquatic ecosystems has attracted increasing attention. However, in treated wastewater, the content of antibiotics is often as low as 10 ppm, and low concentrations of antibiotics are difficult to remove by conventional methods such as membrane filtration, adsorption and electrochemistry. In recent years, photocatalytic technology has been considered a promising method for degrading pollutants due to its advantages such as no secondary pollution risk, environmental sustainability, and environmentally friendly degradation performance.

[0003] In the past, oxides based on transition metals (Fe, Co, Ni) have been studied as catalysts to replace precious metals due to their abundance, low cost, and high catalytic activity. Among them, spinel ferrites have attracted much attention due to their advantages such as high catalytic efficiency, simple preparation, and easy recycling. For example, low-cost spinel ferrite Fe3O4 has been widely reported to have photocatalytic activity and has been used in photocatalytic degradation of dyes. In addition, its excellent stability and magnetism are conducive to the recycling of photocatalytic degradation of wastewater. However, due to the large specific surface area and narrow spectral response of Fe3O4, its photocatalytic performance is still not ideal.

[0004] Therefore, based on the high entropy oxide theory, preparing high entropy spinel ferrites and enhancing their photocatalytic activity is a promising strategy. Summary of the invention

[0005] To solve the above problems, the technical solution of the present invention is: a method for preparing a high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics, comprising the following steps:

[0006] Weigh iron nitrate, nickel nitrate, cobalt nitrate, zinc acetate, and copper nitrate in a molar ratio of 1:1:1:0.76:0.76, and dissolve and mix in deionized water to obtain a metal ion salt solution;

[0007] Weigh glycine at a molar ratio of glycine to metal ions of 1.05:1.04; weigh citric acid at a molar ratio of citric acid to metal ions of 1.09:1.04, dissolve the citric acid and glycine in the metal ion salt solution, and stir until a colloidal solution is obtained;

[0008] The colloidal solution is transferred to an evaporating dish and continues to be heated and evaporated while being stirred. After spontaneous combustion, stirring is stopped and the temperature is naturally lowered after the combustion is completed to obtain a precursor powder.

[0009] The precursor powder is ground and then placed in a high-temperature furnace for calcination at a temperature of 700-900° C. to obtain a high-entropy spinel ferrite catalyst.

[0010] Furthermore, the precursor powder is ground and then placed in a high-temperature furnace for calcination at 800° C. to obtain a high-entropy spinel ferrite catalyst.

[0011] Furthermore, the evaporation time of the colloidal solution in the evaporating dish is 30 min-2 h, the evaporation temperature is 400° C.-500° C., and the stirring speed is 30 rpm.

[0012] Furthermore, during the calcination, the heating rate is 5°C / min, the cooling rate is 5°C / min, and the holding time is 2h.

[0013] Further, the general formula of the high entropy spinel ferrite catalyst is Cu 1 / 2 Zn 1 / 2 Fe 2 / 3 Co 2 / 3 Ni 2 / 3 O4, the catalyst particle size is 50-200nm.

[0014] The high entropy spinel ferrite catalyst degrades antibiotics under light conditions without adding an oxidant, and the antibiotics include tetracycline and cefixime.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] The method provided by the present invention for improving the ability of spinel ferrite to degrade dyes and antibiotics under visible light by using a high entropy strategy:

[0017] (1) This study successfully prepared Cu by sol combustion method 1 / 2 Zn 1 / 2 Fe 2 / 3 Co 2 / 3 Ni 2 / 3 O4 high entropy spinel ferrite catalyst has obvious selective photocatalytic effect on dyes such as methylene blue, and also has certain photocatalytic effect on antibiotics such as tetracycline and cefixime. The degradation efficiency is significantly higher than that of single component oxides.

[0018] (2) After multiple cycles of use, the catalyst still maintains good photocatalytic activity, with a cycle performance of 96.63%.

[0019] (3) A high-entropy strategy was adopted to combine multiple metal elements together to form a high-entropy spinel ferrite catalyst, which fully utilized the high-entropy effect, strong lattice distortion effect, slow diffusion effect and cocktail effect, and significantly improved the photocatalytic performance of the catalyst.

[0020] (4) The presence of metal ions of various valence states in high-entropy spinel ferrite catalysts provides more reaction sites and charge transfer pathways for the catalytic reaction, further improving the catalytic activity.

[0021] (5) The invention uses visible light as energy, avoiding the secondary pollution problem that may be generated in traditional chemical oxidation methods. The high entropy spinel ferrite catalyst has good magnetic properties and is easy to recycle, which is in line with the concept of green environmental protection.

[0022] (6) The high entropy spinel ferrite catalyst is prepared by the sol combustion method, which is simple to operate, low in cost, and easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) is the XRD pattern of spinel oxides J-700, J-800, and J-900 synthesized under different conditions and their corresponding spinel ferrite standard cards, (bc) is the SEM image of high entropy spinel oxide J-800;

[0024] Figure 2 is the concentration variation of different pollutants in photocatalytic degradation C t / C0 graph, a is methylene blue (MB), b is rhodamine B (RhB), c is eosin, d is tetracycline, e is cefixime, and f is the summary of the degradation rates of the five pollutants;

[0025] Figure 3 a. Represents the cycle performance test b. Represents the photocatalytic degradation of methylene blue by high entropy spinel oxide catalyst and single element oxide catalyst c. Represents the pseudo-first-order kinetics of photocatalytic degradation;

[0026] Figure 4 For four components (Co 0.4 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 powder has almost no catalytic degradation effect on TCH in the absence of light and peroxydisulfate (PDS). DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with the embodiments and the accompanying drawings. However, the following description is only for some exemplary embodiments of the present invention and is only used to illustrate the present invention, and is not used to limit the scope of the present invention.

[0028] Example 1

[0029] A high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics and a preparation method thereof, comprising the following steps:

[0030] Accurately weigh 0.023 molFe(NO3)3*9H2O (iron nitrate nonahydrate), 0.023 molNi(NO3)2*6H2O (nickel nitrate hexahydrate), 0.023 molCo(NO3)2*6H2O (cobalt nitrate hexahydrate), 0.0175 molZn(C2H3O2)2*2H2O (zinc acetate dihydrate), 0.0175 molCu(NO3)2*3H2O (copper nitrate trihydrate), and mix and dissolve them thoroughly to obtain a metal salt solution. In this embodiment, Zn(C2H3O2)2*2H2O (zinc acetate dihydrate) is selected for accurate mixing. The weighing ratio is Zn((NO3)2*6H2O, which has high precision and small error. Because Zn((NO3)2*6H2O is easy to deliquesce and its melting point is close to room temperature, it is not easy to weigh accurately. Accurately weigh 0.109 mol of citric acid and 0.105 mol of glycine at 70°C and fully dissolve them. After stirring for 1 hour, add the metal salt solution and mix them thoroughly. The pH of the mixed solution in this embodiment is 4.00-7.00. Stir for 6 hours to obtain a colloidal solution. Transfer the colloidal solution to an evaporating dish and continue heating and evaporating while stirring. Stop stirring after spontaneous combustion. Wait for the combustion to end and then cool down naturally to obtain a precursor powder. The precursor powder (Cu 1 / 2 Zn 1 / 2 Fe 2 / 3 Co 2 / 3 Ni 2 / 3 ) x O y The precursor powder was ground and then calcined in a high-temperature furnace. The precursor powder was calcined at three calcination temperatures of 700°C, 800°C and 900°C for 2 hours respectively to obtain the product Cu 1 / 2 Zn 1 / 2 Fe 2 / 3 Co 2 / 3 Ni 2 / 3O4, the products calcined at different temperatures were named J-700, J-800 and J-900 respectively.

[0031] In this embodiment, Cu 2+ 、Zn 2+ , Fe 3+ 、Co 3+ 、Ni 3+The molar ratio of the salt of the ions is the same as the stoichiometric ratio of each divalent and trivalent metal ion in the chemical formula M3O4 of spinel. The stoichiometric ratio of the above divalent and trivalent metal ions is 1:2, the stoichiometric ratio of each divalent metal ion is the same, and the stoichiometric ratio of each trivalent metal ion is the same. Therefore, the metal salt solution contains five metal ions: Fe 3+ 、Ni 3+ 、Co 3+ 、Zn 2+ , Cu 2+ The molar ratio is 1.00:1.00:1.00:0.76:0.76.

[0032] In aqueous solution, citric acid can lose protons on its carboxyl and hydroxyl groups, and the three carboxyl groups and one or more hydroxyl groups of citric acid can coordinate with metal ions in various ways to form complexes with different compositions and charge states. After citric acid coordinates with metal ions by deprotonating α-alkoxy and α-carboxyl groups, the number of protons on the β-carboxyl group can be adjusted by adjusting the pH value of the solution, so that citric acid-metal ion anion structures with different charges are produced, thereby controlling the composition of the oxide formed subsequently. When the pH is appropriately reduced, on the one hand, the concentration of citric acid is also increased, which will promote the reversible reaction to move in the direction of generating coordination compounds, and on the other hand, citric acid-metal ion anion structures with different charges are formed, which is conducive to the nucleation of crystal nuclei in the subsequent self-combustion process. Insufficient citric acid will make it difficult to form enough coordination compounds on the one hand, and on the other hand, the insufficient combustion heat value may reduce the reaction temperature. Specifically, in this embodiment, 1 mol of Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Zn(C2H3O2)2, Cu(NO3)2 needs 1 mol of citric acid to form a complex with citric acid.

[0033] Therefore, the molar percentages of the five components in the metal salt solution are Fe(NO3)3*9H2O: 7.233%, Ni(NO3)2*6H2O: 7.233%, Co(NO3)2*6H2O: 7.233%, Zn(C2H3O2)2*2H2O: 5.503%, and Cu(NO3)2*3H2O: 5.503%. The molar percentage of glycine is 33.019%, and the ratio of glycine to metal ions is 1.05:1.04; the molar percentage of citric acid is 34.277%, and the ratio of citric acid to metal ions is 1.09:1.04.

[0034] In this embodiment, Fe 3+ 、Ni 3+ 、Co 3+ 、Zn 2+ , Cu 2+, through the self-propagating combustion reaction of glycine and citric acid with nitric acid, Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Zn(C2H3O2)2, Cu(NO3)2 are decomposed into N2, CO2, H2O, and metal oxides. A large amount of heat is released in the reaction. The reaction process is carried out in a mixed solution, which can ensure the accuracy of the stoichiometric ratio and the uniformity of the product composition, so that the oxide is directly crystallized from the mixture of the precursor. The large amount of gas produced by the reaction not only prevents the contact between the particles, but also helps to quickly diffuse the heat generated by the reaction, thereby preventing the sintering of the product and not easily forming hard agglomerates. Organic matter with strong complexing force on metal ions is selected in the mixed solution to avoid precipitation of a certain component crystal during the combustion and volatilization process, which will destroy the overall uniformity.

[0035] The reaction equations of Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Zn(C2H3O2)2, Cu(NO3)2 and citric acid C6H8O7 and O2 to generate Fe2O3, Ni2O3, Co2O3, ZnO and CuO are as follows:

[0036] 4Fe(NO3)3+6C6H8O7+12O2→2Fe2O3+36CO2+24H2O+6N2; the ratio of citric acid to metal salt is 1.5;

[0037] 4Ni(NO3)2+6C6H8O7+18O2→2Ni2O3+36CO2+24H2O+4N2; the ratio of citric acid to metal salt is 1.5;

[0038] 4Co(NO3)2+6C6H8O7+18O2→2Co2O3+36CO2+24H2O+4N2; the ratio of citric acid to metal salt is 1.5;

[0039] 4Zn(C2H3O2)2+2C6H8O7+25O2→4ZnO+28CO2+20H2O; the ratio of citric acid to metal salt is 0.5;

[0040] 4Cu(NO3)2+6C6H8O7+17O2→4CuO+36CO2+24H2O+4N2; the ratio of citric acid to metal salt is 1.5;

[0041] Theoretically, when the five metal ions are prepared into a high entropy material according to the molar ratio in the high entropy material of this embodiment, when the weighted ratio of citric acid to metal salt is 1.33, the metal salt can be completely decomposed to reduce impurities;

[0042] The reaction equations of Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Zn(C2H3O2)2, Cu(NO3)2 and glycine NH2-CH2-COOH to generate Fe2O3, Ni2O3, Co2O3, ZnO and CuO are as follows:

[0043] 2Fe(NO3)3+6NH2CH2COOH+6O2→Fe2O3+12CO2+6N2+15H2O; the ratio of glycine to metal salt is 3;

[0044] 2Ni(NO3)2+2NH2CH2COOH→Ni2O3+4CO2+3N2+5H2O; the ratio of glycine to metal salt is 1;

[0045] 2Co(NO3)2+2NH2CH2COOH→Co2O3+4CO2+3N2+5H2O; the ratio of glycine to metal salt is 1;

[0046] 2Zn(C2H3O2)2+4NH2CH2COOH+17O2→2ZnO+16CO2+2N2+16H2O; the ratio of glycine to metal salt is 2;

[0047] Cu(NO3)2+2NH2CH2COOH+2O2→CuO+4CO2+2N2+5H2O; the ratio of glycine to metal salt is 2;

[0048] Theoretically, when the five metal ions are prepared into a high entropy material according to the molar ratio in the high entropy material of this embodiment, when the weighted ratio of glycine to metal salt is 1.78, the metal salt can be completely decomposed to reduce impurities;

[0049] In this embodiment, Fe 3+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ , adding glycine assists the self-propagating combustion reaction between citric acid and nitrate, so that Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Zn(C2H3O2)2, and Cu(NO3)2 are completely decomposed into N2, CO2, H2O, and metal oxides, reducing impurities.

[0050] Results analysis: Characterization of catalysts J-700, J-800 and J-900

[0051] The results show that high entropy spinel ferrite HEO-FNCCZ can be successfully prepared by calcination at 800℃ or 900℃. The characteristic diffraction peaks at 30.3°, 35.7°, 43.7°, 57.3° and 62.9° correspond to the (220), (311), (400), (511) and (440) crystal planes of cubic Fe3O4, respectively. Figure 1 (a) shows the phase composition of spinel oxides J-700, J-800 and J-900 synthesized under different conditions. By comparing the standard card PDF#26-1136 of spinel Fe3O4, it can be found that the XRD characteristic peaks show that J-800 and J-900 have formed high entropy ferrite, while some characteristic peaks of J-700 are unclear and there are obvious impurities. Figure 1 The (bc) SEM (J-800) images in the figure show that the synthesized catalyst has a uniform particle size of about 50-200nm. There is no obvious agglomeration phenomenon, indicating that the material has good dispersibility, laying the foundation for the subsequent improvement of material performance.

[0052] Example 2

[0053] A high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics and a preparation method thereof, comprising the following steps:

[0054] Accurately weigh 0.023 molFe(NO3)3*9H2O (iron nitrate nonahydrate), 0.023 molNi(NO3)2*6H2O (nickel nitrate hexahydrate), 0.023 molCo(NO3)2*6H2O (cobalt nitrate hexahydrate), 0.0175 molZn(C2H3O2)2*2H2O (zinc acetate dihydrate), 0.0175 molCu(NO3)2*3H2O (copper nitrate trihydrate), mix and dissolve them thoroughly to obtain a metal salt solution, accurately weigh 0.109 mol citric acid and 0.105 mol glycine, fully dissolve them at 60°C-80°C, stir for 1 hour, add the metal salt solution and mix thoroughly, stir for 6 hours to obtain a colloidal solution, transfer the colloidal solution to an evaporating dish, continue heating and evaporating with continuous stirring, stop stirring after spontaneous combustion, wait for the combustion to end and cool naturally to obtain a precursor powder (Cu 1 / 2 Zn 1 / 2 Fe 2 / 3 Co 2 / 3Ni 2 / 3 ) x O y The precursor powder was ground and then calcined in a high-temperature furnace. The precursor powder was calcined at 700°C, 800°C, and 900°C for 2 hours to obtain the catalyst Cu 1 / 2 Zn 1 / 2 Fe 2 / 3 Co2 / 3 Ni 2 / 3 O4.

[0055] Weigh 50 mg of catalyst and pour it into a quartz glass reaction bottle (quartz glass reaction bottle allows light to penetrate and reach the reaction system; it does not react with the reactants to ensure the purity and controllability of the reaction), add 100 ml of the solution to be degraded with a concentration of 10 ppm to the bottle and shake it well, put the reaction bottle into a dark box for adsorption for 12 hours, and then move it to the photocatalytic equipment (PerfectLight, PCX50CDiscover) for photocatalytic reaction, and start stirring at the same time. The photocatalytic degradation process and sampling operations are carried out in a 25°C constant temperature circulating water environment. The experiment takes out 3-4 mL of the test solution every 1 hour. Methylene blue, rhodamine B, eosin, and tetracycline are measured by ultraviolet spectrophotometry. The test solution is collected by Shimadzu UV-1900i spectrometer with a scanning width of 400-800 nm UV-visible spectrum, and cefixime is collected by Agilent 1260InfinityII liquid chromatograph at 258 nm to obtain the pollutant concentration change C t / C0.

[0056] Result analysis: Effect of calcination temperature on the photocatalytic degradation performance of catalysts

[0057] In this experiment, three commonly used industrial dyes, methylene blue (MB), rhodamine B (RhB), and eosin, and two antibiotics, tetracycline and cefixime, were selected as degradation substrates to explore the photocatalytic performance of HEO-FNCCZ. Figure 2 As shown in Figures a to f, under each degradation substrate, the photocatalytic degradation efficiency of J-700, J-800, and J-900 showed similar patterns. On the one hand, the three showed that with the increase of reaction time, the substrate concentration decreased, and the catalytic degradation rate decreased. On the other hand, in each group of experiments, J-800 showed a better photocatalytic degradation performance. For example, in the photocatalytic degradation experiment of methylene blue with the best effect, the C of J-800 group was 2.34 wt. % after 7 h. t / C0 is 5.81% lower than that of J-700 group. The experimental results of photocatalytic degradation of dyes show that the high entropy spinel catalyst has a significant selective catalytic degradation effect on dyes, among which the catalytic degradation efficiency of methylene blue is the highest. After 6h and 7h of visible light irradiation, the MB concentration in water of J-800 dropped to 6.16% and 3.25%, respectively; the catalyst has no significant photocatalytic degradation effect on rhodamine B and eosin. The experimental results of photocatalytic degradation of antibiotics show that the high entropy spinel catalyst has a good photocatalytic degradation effect on tetracycline and cefixime. After 6h of visible light irradiation, the concentrations of tetracycline and cefixime dropped to 34.4% and 19.0% of the initial concentrations, respectively.

[0058] Example 3

[0059] Accurately weigh 0.023 molFe(NO3)3*9H2O (iron nitrate nonahydrate), 0.023 molNi(NO3)2*6H2O (nickel nitrate hexahydrate), 0.023 molCo(NO3)2*6H2O (cobalt nitrate hexahydrate), 0.0175 molZn(C2H3O2)2*2H2O (zinc acetate dihydrate), 0.0175 molCu(NO3)2*3H2O (copper nitrate trihydrate), mix and dissolve them thoroughly to obtain a metal salt solution, accurately weigh 0.109 mol citric acid and 0.105 mol glycine, fully dissolve them at 70°C, stir for 1 hour, then add the metal salt solution and mix thoroughly, stir for 6 hours to obtain a colloidal solution, transfer the colloidal solution to an evaporating dish, continue heating and evaporating with continuous stirring, stop stirring after spontaneous combustion, wait for the combustion to end, and cool naturally to obtain a precursor powder. The precursor powder was ground and calcined in a high-temperature furnace. The precursor powder was calcined at three calcination temperatures of 700°C, 800°C, and 900°C for 2 hours to obtain the catalyst. The single element oxide MxOy (M = Fe, Co, Ni, Cu, Zn) was synthesized using the same combustion process, and the photocatalytic degradation experiment was carried out under the same reaction conditions. 50 mg of high entropy catalyst and single oxide catalyst were weighed and poured into a quartz glass reaction bottle, and 100 ml of 10 ppm solution to be degraded was added to the bottle and shaken. The reaction bottle was placed in a dark box for adsorption for 12 hours, and then transferred to a photocatalytic device (PerfectLight, PCX50CDiscover) for photocatalytic reaction, and stirring was turned on. The photocatalytic degradation process and sampling operations were carried out in a 25°C constant temperature circulating water environment. 4-5 mL of the solution to be tested was taken out every 1 hour in the experiment. Methylene blue was measured by ultraviolet spectrophotometry. The test solution was collected by Shimadzu UV-1900i spectrometer in the range of 400-800nm ​​scanning width to obtain the absorbance A at the maximum absorption peak. t The same method is used to collect the standard solution and obtain the maximum absorbance A0 at the initial concentration. When the time is t, the residual amount of pollutants is C t / C0.

[0060] The formula is as follows:

[0061] (C t / C0)×100%=A t / εb / C0=(A t / A0)×100%

[0062] C0: initial concentration, C t : Real-time concentration, A t: absorbance, b: wavelength, ε: molar absorption coefficient;

[0063] Result analysis: Comparison of photocatalytic effects of high entropy catalyst and single oxide with methylene blue as substrate

[0064] The photocatalytic degradation performance of high entropy catalysts is significantly better than that of single element oxides, among which J-800 with the best performance has a C t / C0 reaches 3.25%, compared with the worst performance of Fe2O3 at 7h C t / C0 was 40.38%, and the performance was improved by 38.29%. The other groups were CuO at 7h and C t / C0 is 19.85%, ZnO C t / C0 is 7.05%, Co3O4 C at 7h t / C0 is 31.94%. On the other hand, in the photocatalytic degradation experiment, the amount of catalyst added was 50 mg, while the molecular weight of the high entropy catalyst was 244.12 and the molecular weight of Fe2O3 was 159.7. Under the same mass, the catalyst molar ratio was 0.6542, that is, the photocatalytic degradation performance of methylene blue per mole of high entropy catalyst was 58.53% higher than that of Fe2O3 per mole. Figure 3 As shown in a, the cyclic performance of the catalyst was verified by recycling and repeating the photocatalytic degradation experiment of methylene blue. After the fourth cycle, the C t / C0 increased from 0.0741 to 0.0716, and the cycle performance reached 96.63%, indicating that the high entropy ferrite catalyst has excellent cycle performance. Kinetic analysis of photocatalytic degradation of methylene blue Figure 3 The specific data are shown in Table 1.

[0065] The Langmuir-Hinshelwood (LH) first-order reaction kinetic rate equation at the liquid-solid interface is approximately:

[0066]

[0067] Where t is the illumination time, and the apparent constant K app As the basic kinetic parameters of different photocatalysts. The LH model was used to calculate the K of methylene blue degradation rate under different conditions. app and the regression coefficient R 2 . R 2 The value is greater than 0.95, indicating that the LH equation is suitable for the photocatalytic degradation of methylene blue, ln(C t / C0) and t curves show a good linear relationship.

[0068] Table 1. Kinetic data of photocatalytic degradation of methylene blue by catalysts

[0069]

[0070] Comparative Example 3

[0071] According to (Co 0.4 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 in a stoichiometric ratio (i.e., 0.4:0.2:0.2:0.2:2, x=0.4) Cobalt nitrate, nickel nitrate, zinc nitrate, copper nitrate and iron nitrate are weighed, and the resulting mixture is mixed with distilled water; in addition, glycine fuel is added according to the chemical equation for complete combustion reaction, and the molar ratio of nitrate ion to glycine is 2.5:1, and stirred to completely dissolve it to obtain a mixed solution. The pH value of the mixed solution is adjusted to 4.7 with ammonia water to obtain a precursor solution, and the precursor solution is transferred to a quartz crucible and heated on an electric furnace to evaporate the water and finally cause a combustion reaction to obtain a precursor powder. The obtained precursor powder is placed in a muffle furnace and kept at 1100°C for 3 hours for powder heat treatment to obtain a four-component (Co 0.4 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 powder, and tested the performance of the powder in degrading antibiotics. The results are as follows Figure 4 The reaction process is as follows: 240 mL of tetracycline hydrochloride solution (TCH, concentration is 50 mg / L) is taken, four components (Co 0.4 Ni 0.2 Zn 0.2 Cu 0.2 )Fe2O4 powder concentration is 0.5g / L. The removal rate (Rev(%)) of the simulated target pollutant TCH can be calculated using the following formula:

[0072] Rev(%)=(1-C t / C0)×100%=(1―A t / A0)×100%#(1)

[0073] Among them C t represents the concentration of organic pollutants in the filtrate at a certain moment; C0 represents the initial concentration of organic pollutants; A t It indicates the absorbance at the maximum absorption wavelength of organic pollutants in the filtrate at a certain moment (the characteristic absorption peak of tetracycline hydrochloride is 359nm); A0 indicates the absorbance at the maximum absorption wavelength of the initial organic pollutants. Figure 4 It can be seen that the four components (Co 0.4 Ni 0.2 Zn 0.2 Cu 0.2)Fe2O4 powder has almost no catalytic degradation effect on TCH in the absence of light and peroxydisulfate (PDS), but has a certain photocatalytic degradation effect on TCH under light, but the effect is poor and still lower than the photocatalytic degradation effect of the high entropy spinel catalyst on tetracycline in Example 2.

Claims

1. A method for preparing a high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics, characterized in that: The steps include: Weigh iron nitrate, nickel nitrate, cobalt nitrate, zinc acetate, and copper nitrate in a molar ratio of 1:1:1:0.76:0.76, and dissolve and mix in deionized water to obtain a metal ion salt solution; Weigh glycine at a molar ratio of glycine to metal ions of 1.05:1.04; weigh citric acid at a molar ratio of citric acid to metal ions of 1.09:1.04, dissolve the citric acid and glycine in the metal ion salt solution, and stir until a colloidal solution is obtained; The colloidal solution is transferred to an evaporating dish and continues to be heated and evaporated while stirring. After spontaneous combustion, stirring is stopped and the temperature is naturally lowered after the combustion is completed to obtain a precursor powder. The precursor powder is ground and then placed in a high-temperature furnace for calcination at a temperature of 700-900° C. to obtain a high-entropy spinel ferrite catalyst.

2. The method for preparing a high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics according to claim 1, characterized in that: The precursor powder is ground and then placed in a high-temperature furnace for calcination at 800° C. to obtain a high-entropy spinel ferrite catalyst.

3. The high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics and the preparation method thereof according to claim 1, characterized in that: The colloid solution is evaporated in an evaporating dish for 30 min-2 h, at a temperature of 400° C.-500° C., and at a stirring speed of 30 rpm.

4. The method for preparing a high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics according to claim 1, characterized in that: During the calcination, the heating rate is 5°C / min, the cooling rate is 5°C / min, and the holding time is 2h.

5. The high entropy spinel ferrite catalyst for efficiently degrading dyes and antibiotics prepared by the method according to claim 1, characterized in that: The general formula of the high entropy spinel ferrite catalyst is Cu 1 / 2 Zn 1 / 2 Fe 2 / 3 Co 2 / 3 Ni 2 / 3 O4, the catalyst particle size is 50-200nm.

6. Use of the high entropy spinel ferrite catalyst as claimed in claim 5 to degrade antibiotics without adding an oxidant under light conditions.

7. The use according to claim 6, characterized in that The antibiotics include tetracycline and cefixime.

Citation Information

Patent Citations

  • Preparation method and application of porous magnetoplumbite barium ferrite

    CN107684893A

  • High-entropy catalyst for photo-thermal synergistic degradation of VOCs (Volatile Organic Compounds) at low temperature and preparation method thereof

    CN117225433A

  • Low-temperature sintered NiCuZn ferrite material and its preparation method

    CN1631839A

  • PHOTOCATALYTIC composition COMPRISING METALLIC PARTICLES AND TWO SEMI-CONDUCTORS INCLUDING ONE IN CERIUM OXIDE

    FR3026964A1

  • Method of producing hybrid photocatalyst surface agent and hybrid photocatalyst surface agent made thereby

    KR1020110093108A

Cited By

  • Method for synthesizing ZnFe2O4 photocatalyst based on ferromagnetic resonance absorption effect mediation

    CN121819841A